2006
DOI: 10.1577/m05-110.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an Unsuccessful Brook Trout Electrofishing Removal Project in a Small Rocky Mountain Stream

Abstract: Abstract.-In the western United States, exotic brook trout Salvelinus fontinalis frequently have a deleterious effect on native salmonids, and biologists often attempt to remove brook trout from streams by means of electrofishing. Although the success of such projects typically is low, few studies have assessed the underlying mechanisms of failure, especially in terms of compensatory responses. A multiagency watershed advisory group (WAG) conducted a 3-year removal project to reduce brook trout and enhance nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
112
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(118 citation statements)
references
References 43 publications
6
112
0
Order By: Relevance
“…Of the case studies examined, 16 showed evidence of compensatory recruitment (Table 3. 1). Of case studies showing signs of compensation, the increase in juvenile and overall abundance was sufficient in five cases to suggest overcompensation may have occurred (Smith et al 1996, Meyer et al 2006, Weidel et al 2007, Thuesen et al 2011, Shepard et al 2014. The majority of unsuccessful removal efforts showed evidence of compensation (Fisher's exact p < 0.001; Table 3.2), though compensation appeared to have occurred in a few efforts that resulted in the successful reduction or eradication of the target species.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…Of the case studies examined, 16 showed evidence of compensatory recruitment (Table 3. 1). Of case studies showing signs of compensation, the increase in juvenile and overall abundance was sufficient in five cases to suggest overcompensation may have occurred (Smith et al 1996, Meyer et al 2006, Weidel et al 2007, Thuesen et al 2011, Shepard et al 2014. The majority of unsuccessful removal efforts showed evidence of compensation (Fisher's exact p < 0.001; Table 3.2), though compensation appeared to have occurred in a few efforts that resulted in the successful reduction or eradication of the target species.…”
Section: Resultsmentioning
confidence: 98%
“…Similarly, removal of brook trout, Salvelinus fontinalis, resulted in a 789% increase in individuals < 1 year old, comprising an estimated 74% of the population, up from 16% at the beginning of electrofishing efforts (Meyer et al 2006). If overcompensation occurred in Bodega Harbor with similar impacts, our model would be capable of detecting the ensuing demographic shift.…”
Section: Contrary To Our Findings Bückman and Adelung (1964) Found Tmentioning
confidence: 97%
See 3 more Smart Citations